Machine learning based analysis and prediction of crop yield and prices of Aman, Aus and Boro rice - Bhattacharjee, Ruposri; Mamun, Kazi Andelib; Asif, Kazi Saad; Khan, Shaian (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.